1995
DOI: 10.1107/s0909049595008156
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Photoemission from Complex Cuprates and Nickelates

Abstract: Synchrotron-excited resonant-photoemission measurements at rare-earth 4d ~ 4fand transition-metal 3p ~ 3d thresholds have been carried out using a variety of complex cuprates and nickelates on stations 6.1 (grazing-incidence monochromator) and 6.2 (toroidal-grating monochromator) at the SRS CLRC Daresbury Laboratory. The systems studied are Nd2Nil _xCuxO4, La2_xSrxNil _yFeyO4 + 6 and Bi2Sr/Cal_xYxCu208 + 6. A combination of EDC and constant-initial-state data is used to examine the 4f and 3d contributions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…The effect of doping Sr for La is to increase the oxidation states of Ni and Fe, so that it is possible to generate unusually high Ni(III) and Fe(IV) valences [7]. Resonant photoemission for this system shows that the part of the valence band closest to the Fermi energy has both Ni and Fe character, consistent with the ease with which these cations may be oxidised in the catalyst [3,8]. When the xy0 material is doped with Sr (increasing the Ni valency), we see a movement of the valence band edge towards the Fermi level (Figs.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The effect of doping Sr for La is to increase the oxidation states of Ni and Fe, so that it is possible to generate unusually high Ni(III) and Fe(IV) valences [7]. Resonant photoemission for this system shows that the part of the valence band closest to the Fermi energy has both Ni and Fe character, consistent with the ease with which these cations may be oxidised in the catalyst [3,8]. When the xy0 material is doped with Sr (increasing the Ni valency), we see a movement of the valence band edge towards the Fermi level (Figs.…”
Section: Resultsmentioning
confidence: 70%
“…Model catalysts have been prepared and investigated using resonant photoemission spectroscopy to determine the nature of the density of states at the Fermi level [3]. A co-precipitation route from soluble metal salts (LaCl 3 , Sr(NO 3 ) 2 , NiCl 2 and Fe(NO 3 ) 3 ) in their required molar ratios with sodium carbonate was used.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Fig. 5b, the observed resonance was weak similarly as in La 1 À x Sr x Ni 1 À y Fe y O 4 + d at the Ni 3p-3d threshold (Flavell et al, 1995). One of the reason of these results can be the small amount of nickel species at the film surface.…”
Section: Valence Band Spectramentioning
confidence: 63%
“…O 2ps) states at around 5-7 eV (Park et al, 2004;Mullica et al, 1993) participate in the observed VB enhancement, while peak at around 3 eV corresponding to nonbonding O 2pp molecular orbital is actually insensitive to resonant La 4d-4f excitation. Flavell et al (1995) reported the resonant photoemission study of La 1À x Sr x Ni 1À y Fe y O 4+ d , at the Ni 3p-3d threshold. The observed resonance was considerably weaker than for the d-f transition, but it is nevertheless seen clearly in the CIS data.…”
Section: Valence Band Spectramentioning
confidence: 99%
“…3) reveals an anti-resonance. This destructive interference, which takes place when one of the photoemission channels is suppressed, has been observed in the valence band photoemission of a number of correlated oxides, including cuprates and nickelates [23,24]. Typically, resonance of so-called 'satellite' features at around 12 eV BE has been associated with an unscreened photoemission final state 3d n−1 , whereas the majority valence band structure arises from the screened final state 3d n L 1 (where L implies a ligand hole, i.e.…”
Section: General Features Of the Valence Band Spectramentioning
confidence: 92%